Further improvements of determinization methods for fuzzy finite automata - Jančić, Zorana; Micić, Ivana; Ignjatović, Jelena; Ćirić, Miroslav (Fuzzy sets and systems, 2016)
In this paper we provide further improvements of determinization methods for fuzzy finite automata. These methods perform better than all previous determinization methods for fuzzy finite automata, developed by Bělohlávek [3], Li and Pedrycz [38], Ignjatović et al. [25], and Jančić et al. [33], in the sense that they produce smaller automata, while require the same computation time. The only exception is the Brzozowski type determinization algorithm developed recently by Jančić and Ćirić [34], which produces a minimal crisp-deterministic fuzzy automaton, but the algorithms created here can also be used within the Brzozowski type algorithm and improve its performance.